Bespoke sodium supplementation increases physical performance - Weatherall, L.; Jutley, R. S.; Blow, A.; Nanjaiah, P.; Voysey, V. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
The loss of sodium during exercise has significant effects on performance ranging from mild cognitive impairment to fatal hyponatraemia. Sodium losses in human sweat vary 9-fold(1, 2) which when considering the high variation in sweat losses can lead to massive net sodium losses as high as 13-fold between athletes in the same session(3). In this study we evaluate the influence of replacing sweat sodium losses using a bespoke sodium electrolyte solution based on individual sweat sodium levels on physical performance under controlled conditions. Methods: Randomised crossover study comparing H2ProHydrate (500, 1000 or 1500 mg/l sodium) to Evian water (5mg/L sodium) in 7 elite male athletes. Pre-trial all underwent V02 max testing and the Precision Hydration pilocarpine-induced sweat sodium analysis. Randomisation was to water or H2ProHydrate allowing ad libitum drinking for 72 hrs pre-trial. Cross-over was undertaken 2 weeks later. Athletes maintained 70% VO2 max in a climate chamber at 28C, 55% humidity for 60 min followed by a 15-min blinded performance time trial (TT). End points included power output during chamber exposure and TT, RPE (Borg Scale), heart rate (HR), core body temperature (CBT) and lactate levels. Results: Mean sweat sodium concentration was 1043mg/L (range 430-1640). One athlete failed to complete the trial while on water due to nausea and dizziness and was therefore excluded from analysis. Chamber Exposure The athletes were expected to maintain an output of 70% VO2 max equating to 233 W. On H2Pro the group maintained 215 W and on water alone, 206 W (a 4.4% performance gain). The mean RPE was similar in both groups(16.27 on water, 16.03 on H2Pro). Mean heart rates were 4.3% lower with H2Pro compared to water (162/min vs. 169/min) as was mean CBT (38.4C vs. 38.6C). Mean lactate levels were similar; 4.8 mmol/L H2Pro, 4.7 mmol/L water Performance Time Trial During the blinded TT, athletes on H2Pro demonstrated a 7.3% performance gain compared to water (235 W vs. 219 W) Conclusion: Compared to water, appropriate sodium supplementation increases performance during severe sustained exercise in the heat and during blinded performance time trials by 4.4% and 7.3% respectively. During sustained exercise the gains are seen while maintaining a lower heart rate and core body temperature and the equivalent lactate and RPE. Our study indicates that appropriate sodium supplementation maintains a more physiological state during extreme exercise.